Ecthyma gangrenosum: a report of eight cases - Martínez Longoria, César Adrián; Rosales Solis, Gloria María; Ocampo Garza, Jorge; Guerrero González, Guillermo Antonio; Ocampo Candiani, Jorge (2017)
Abstract: Ecthyma gangrenosum is a rare skin infection classically associated with Pseudomonas aeruginosa. We performed a retrospective study of all cases diagnosed with ecthyma gangrenosum from 2004-2010 in a university hospital in Mexico (8 cases, 5 female patients and 3 male patients, ages between 4 months and 2 years). The most common risk factor for ecthyma gangrenosum is neutropenia in immunocompromised patients. In previously healthy patients, immunological evaluation is important to rule out underlying immunodeficiency. Ecthyma gangrenosum in healthy patients has a high mortality rate and early diagnosis and aggressive antibiotic treatment is imperative as it can improve patients’ prognosis. Keywords: Ecthyma; Pseudomonas; Pseudomonas aeruginosa; Pseudomonas infections